Enhanced Recovery of Bioactive Compound from Pineapple Peel Using Ultrasonic-Assisted Extraction with Enzyme Treatment at Varying Extraction Time - Kumalaningrum, Amalia Nur; Arini, Zulmilafatma Nurlita; Hidayat, Jefri Pandu (Indonesian Journal of Chemical Research, 2025)
Pineapple peel is considered waste, but it has numerous beneficial uses due to its rich content of nutrients and bioactive compounds. The selection of extraction methods is essential to produce optimal bioactive compound extracts. Ultrasonic-assisted extraction (UAE) is a modern extraction technique that uses ultrasonic waves to improve the extraction by enhancing the release of compounds into the solvent. The UAE method was performed by varying extraction times at 30, 60, 90, and 120 min. The addition of cellulase enzyme was also applied as an optimization method for the extraction results. The addition of Cellulase elevated the yield, phenolic, and flavonoid content. The highest yield was obtained at an extraction time after 90 min. The highest total flavonoid content was 497.8±4.5 µgQE/mL, while the highest total phenolic value was 1007.6±7.6 µgGAE/mL at extraction of 60 min. However, the extracted samples without enzymes performed the highest results at an extraction of 90 min. The effect of the enzyme resulted in the most potent antioxidant activity (<10 ppm) in all-time extraction. To conclude, the addition of enzymes in the extraction process successfully optimized the extraction of phytochemical compounds from pineapple peel, as evidenced by testing phenolic and flavonoid content and antioxidant activity.